Clinical Characteristics and Outcomes of Women Presenting with Venous Thromboembolism during Pregnancy and Postpartum Period: Findings from the RIETE Registry - Elgendy, Islam Y.; Fogerty, Annemarie; Blanco-Molina, Ángeles; Rosa, Vladimir; Schellong, Sebastian; Skride, Andris; Portillo, José; Lopez-Miguel, Patricia; Monreal, Manuel; Weinberg, Ido (Thrombosis and Haemostasis, 2020)
Although venous thromboembolism (VTE) is a leading cause of maternal mortality, there is a paucity of real-world clinical data on clinical presentation and management of VTE during pregnancy and postpartum period. Using data from the international RIETE (Registro Informatizado Enfermedad Trombo Embólica) registry, pregnant and postpartum women with VTE were identified. Baseline characteristics, risk factors, therapies, and outcomes were compared. From March 2001 to July 2019, 596 pregnant and 523 postpartum women had symptomatic, objectively confirmed VTE. Pregnant or postpartum women were less likely to have another risk factor for VTE (i.e., immobility, cancer, recent travel) than nonpregnant women aged < 50 years. The prevalence of thrombophilia was higher among pregnant and postpartum women compared with nonpregnant women (53.2% vs. 46%). Pulmonary embolism (PE) was less commonly diagnosed in pregnant versus postpartum women (27% vs. 42%). Pregnant women with PE were commonly treated with low molecular weight heparin (73% vs. 29%), and received more inferior vena cava filters (6.0% vs. 4.2%) compared with postpartum women. By 90 days, one pregnant and one postpartum woman died after PE, and one died after a deep venous thrombosis. The incidence of recurrent VTE was low. In this largest cohort of pregnant and postpartum women with confirmed VTE, we found that pregnant and postpartum women with VTE were unlikely to present with other risk factors for VTE. Adverse outcomes in our study were uncommon.
Keywords: pregnancy; postpartum; pulmonary embolism; venous thromboembolism